Chapter Optimization model for a hybrid photovoltaic/cold ironing system: life cycle cost and energetic/environmental analysis - Tagliolini, Eleonora (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Cold ironing provides for powering berthed ships in port with electricity from the national grid. A local energy production improves the self-sufficiency of the port area. This work presents an optimization model for a photovoltaic/cold ironing system. The energy demand of ferries was analyzed, taking the port of Ancona (Italy) as case study. The model returns the optimal size of the PV plant based on a Life Cycle Cost (LCC) approach. Results show that the optimal PV plant size is 2100kW and 3700kW for two scenarios with different costs. CO2 emissions saving is 64.9% and 73.1%, respectively